Analisis Mutu Pelayanan Terhadap Kepuasan Pasien (Studi Pada Praktek Umum dr. Fauzan) - Fauzan, Fauzan; Purwoko, Purwoko; Setyawan, Rai Rake (Otonomi, 2024)
Health services are a service that is quite important and strategic, because it concerns the lives and souls of many people. For this reason, quality service products from this service provider are absolutely necessary so that patient satisfaction can be realized. This study aims to determine the relationship between service quality and patient satisfaction at dr. Fauzan, Bantul. This research uses quantitative methods and the data collection tool is a Likert scale, which includes a scale for service quality and patient satisfaction. The number of respondents in this study was 100 people, namely visitors to the practice of dr. Fauzan is over 17 years old and has received services at least twice at this practice. The sampling technique in this research uses non-probability sampling, namely purposive sampling. The data analysis technique in this research uses multiple regression analysis. The research results show that first, physical evidence has a positive and significant effect on patient satisfaction, second, service quality including physical evidence, reliability, responsiveness, assurance and empathy together have a positive and significant effect on patient satisfaction as evidenced by the calculated F value of 6.004 and significance 0.000 < 0.05.